2019
DOI: 10.1186/s12889-019-7499-1
|View full text |Cite
|
Sign up to set email alerts
|

Foundational knowledge regarding childhood obesity: a cross-sectional study of medical students

Abstract: Background Documentation and diagnosis of childhood obesity in primary care is poor and providers are often unfamiliar with guidelines. This lack of knowledge may be attributed to insufficient training in medical school and residency; however, no studies have evaluated medical students’ knowledge of recommendations. Methods We distributed a modified version of the Physician Survey of Practice on Diet, Physical Activity, and Weight Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Similar findings of deficient knowledge and awareness of obesity have been reported of first through 4 th -year medical students regarding screening recommendations and identification of BMI percentile cutpoints in children. [ 12 ] Another study found that the 1 st year medical students scored significantly less (48%) than final year students (60%), their knowledge of the etiology, diagnosis, and treatment of obesity being inadequate. [ 11 ] This difference in the knowledge of obesity has also been observed in primary care providers and nurses, and it has been suggested that additional educational training could enhance their confidence in the management of patients' weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings of deficient knowledge and awareness of obesity have been reported of first through 4 th -year medical students regarding screening recommendations and identification of BMI percentile cutpoints in children. [ 12 ] Another study found that the 1 st year medical students scored significantly less (48%) than final year students (60%), their knowledge of the etiology, diagnosis, and treatment of obesity being inadequate. [ 11 ] This difference in the knowledge of obesity has also been observed in primary care providers and nurses, and it has been suggested that additional educational training could enhance their confidence in the management of patients' weight.…”
Section: Discussionmentioning
confidence: 99%
“…Although the problem of obesity with its attendant comorbidities continues to increase throughout the world, medical students in universities have neither the knowledge nor an appreciation of this problem. [ 10 11 12 ] One important consequence of this lack of awareness is the failure to identify obesity, resulting in inaction on part of an individual. [ 13 ] Cues of personal relevance or an accumulation of cues are likely to motivate one to take action and modify one's health behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, improved knowledge could be a fundamental factor in regulating people's practice and habits ( 44 , 45 ). According to previous findings, students were generally unfamiliar with the advice on the prevention and treatment of childhood obesity and could not identify age-appropriate cut-off points for weight status ( 46 ). Enhancing health-related knowledge was, therefore a necessary element to reduce childhood obesity effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, there is a paucity of training in comprehensive obesity treatment for health professionals, including primary care providers (57,58). In addition, weight bias is high among health professionals, compromising quality of care and potentially reinforcing negative psychosocial sequalae associated with obesity (32).…”
Section: Supporting Appropriate Obesity Carementioning
confidence: 99%